The Impact of International Research Collaborations on the Citation Metrics and the Scientific Potential of South American Palliative Care Research: Bibliometric Analysis - Crislaine de Lima; Bianca Sakamoto Ribeiro Paiva; Martins Fideles dos Santos Neto; David Hui; Pedro Emilio Perez-Cruz; Camilla Zimmermann; Eduardo Bruera; Carlos Eduardo Paiva (Ubiquity Press, 2021)
Background: Progress in palliative care (PC) requires scientific advances which could potentially be catalyzed by international research collaboration (IRC). It is currently not known how often IRC occurs with PC investigators in South America. Objectives: To evaluate the percentage of South America journal articles on PC involving IRCs and the impact of these collaborations on the scientific potential the studies and on their citations. Methods: This was a bibliometric analysis of studies published between January 1, 1998, and December 31, 2017. A search of Pubmed, Embase, Lilacs, and Web of Science (WOS) was performed using the terms "palliative care," "hospice care," "hospices" and "terminal care," combined with the name of South America countries. The scientific potential was assessed by analyzing study design, characteristics of the journal and funding. IRCs were further subdivided in internal (within South America countries) and external (with countries outside South America). Findings: Of the 641 articles, 117 (18.2%) involved IRCs (internal: 18, 2.8%; external: 110, 17.2%). Articles with IRCs had higher median two-year citations in WOS (2 vs. 1, p < 0.001), Scopus (3 vs. 1, p < 0.001) and Google Scholar (4.5 vs. 2, p < 0.001) compared to articles without IRC. Moreover, they were more often funded (40.7% vs. 9.7%, p < 0.001), published in Pubmed-indexed (76.1% vs. 41.6%; p < 0.001) and in WOS-indexed (70.1% vs. 29.6%; p < 0.001) journals, and with study designs most often classified as clinical trial (5.1% vs. 1.0%; p = 0.002) and cohort (10.3% vs. 2.9%; p < 0.001) compared to articles without IRC. Conclusions: Studies with international research collaborations, both internal and external to South America, are more frequently cited and have characteristics with greater scientific potential than do studies without international collaborations.